Bibliometric Mapping of Publication Trends on the Use of Learning Media and Character Values in the Scopus Data Base From 2013 to 2022 - Salmia Salmia; Hartono Bancong; Sudarmin Sudarmin (Yayasan Keluarga Guru Mandiri, 2023)
This study aims to find a map of the development of research in the field of learning media and character values in the Scopus database from 2013 to 2022. The research was carried out by searching through the Scopus database with the keywords 'learning media' and 'character values'. The data was processed and analyzed using the VOSViewer application program to determine the bibliometric map of learning media research developments and character values. The results of the research show that the number of research publications in the field of learning media and character values in Scopus in 2013-2022 has been published from year to year. The largest contributor to publications indexed on Scopus is Universitas Negeri Jakarta. The most productive foreign researcher is from the United Kingdom. The most productive researcher from Indonesia is Mulyati. Researchers in the field of learning media and character values mostly collaborate with the community from Taiwan followed by the community from Australia. Most subjects are teaching and education. Through network visualization, it shows that the map of research development in the field of learning media and character valuesis divided into 7 clusters. The theme of using instructional media and character values can be an opportunity for further research.